Synchrotron X-ray diffraction studies of the phase-specific deformation in additively manufactured Ni–CrC composites. (1st October 2021) - He, Lewei; Pagan, Darren C.; Nardi, Aaron; Hassani, Mostafa
Abstract: Cold spray is a promising solid-state additive manufacturing process for the fabrication of metal matrix composites in the forms of coatings, and more recently, bulk materials, particularly when deposition of two phases is needed with minimal alterations of the chemistry and phase composition. While prior studies have reported improved mechanical performance in cold sprayed composites, a fundamental understanding of the response and contribution of individual constituent phases to the collective mechanical properties of the composite is yet to be developed. In this work, we use in-situ synchrotron X-ray diffraction to study the strain partitioning between the soft and hard phases in cold sprayed Ni–CrC bulk composites. We conduct stepwise uniaxial tensile loading experiments and use high energy X-ray diffraction at multiple load steps to measure phase-specific strains and stresses upon loading. We find neither plasticity in the Ni phase nor a significant load transfer or redistribution between Ni and CrC phases during the loading process and attribute them to a premature failure governed by the presence of defects.